The Phenomenon Of Community Diseases (Beggars) On The Seafront Of Padang Beach - Yuhelna, Yuhelna; Erningsih, Erningsih; Izzati, Fahira Nur; Ardila, Ardila; Syahira, Vaura; Pratama, Karel Gusmin Rahmat; Huwaida, Wulan Ariqah (Universitas PGRI Sumatera Barat, 2024)
Community ills such as beggars on the waterfront (seaside) in Padang are a social issue that requires special attention. This research aims to determine the factors that cause the presence of beggars on Padang beaches, the factors that cause beggars to quit their profession, the life patterns of beggars on Padang beaches, and the impact that beggars have on visitors to Padang beaches. The research method used is a qualitative approach using observation, interview and documentation study techniques. The socio-economic impact that arises is the emergence of social inequality, decreased community productivity, and an increase in the government's burden in dealing with these social problems. Comprehensive efforts are needed from the government and community to overcome the phenomenon of begging on the Padang seafront, such as empowering the community's economy, increasing access to education and skills training, as well as strict law enforcement.